Antibacterial Activity of Eel (Anguilla spp.) Mucus against Salmonella typhi - Tomy Nurtamin; Resty Yulianita Nurman; Indria Hafizah (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Typhoid fever has become one global health problem. Typhoid fever is caused by a Gram-negative bacterium, Salmonella typhi. Eel (Anguilla spp.) is a fish which lives in the sea or in freshwater. Several previous studies have found that Anguilla spp. mucus has the ability as antibacterial against Gram-positive and negative. Although the antibacterial activity of Anguilla spp. against various pathogens had been reported, very little is known about its activity against Salmonella typhi. The aim of this study was to investigate antibacterial activity of Anguilla spp. mucus against Salmonella typhi bacteria.METHODS: Present study was an experimental in vitro test. Antibacterial activity assays were carried out by the disc diffusion method. Antibacterial activity was determined by the clear zone formed around the paper disc and minimum inhibitory concentration was determined by observing the lowest concentration which could inhibit the growth of Salmonella typhi.RESULTS: Result of the present study showed that the Anguilla spp. mucus has inhibitory effects against Salmonella typhi. Minimum inhibitory concentration from the Anguilla spp. mucus was 12.5%.CONCLUSION: Anguilla spp. mucus has antibacterial activity against the Salmonella typhi bacteria.KEYWORDS: eel fish mucus, Anguilla spp., antibacterial activity, Salmonella typhi